Enfermedad arterial periférica asintomática, estimada mediante el índice tobillo-brazo, en pacientes con factores de riesgo cardiovascular hospitalizados en el Área de emergencia del Hospital Manuel Ygnacio Montero de la ciudad de Loja. - Achupallas España, Pablo Ignacio (2016)
Peripheral arterial disease is commonly undiagnosed and often confused with other clinical conditions affecting the lower limbs. For this reason the objective of this study was to determine the prevalence of asymptomatic peripheral arterial disease in patients with cardiovascular risk factors hospitalized in the emergency area of the Hospital Manuel Ygnacio Montero city of loja. a cross-sectional, observational study, implemented in the emergency area, for data collection randomly patients of both sexes over 50 years with cardiovascular risk factors were selected, was performed on 100 patients were included who met with the inclusion criteria. The results were presented in two blocks corresponding to the first cardiovascular risk factors and the second measuring the ankle-arm index. of the 100 patients 41 (41%) are women and 59 (59%) men with average age of 74 years. among the risk factors are arterial hypertension 67%, 37% diabetes mellitus, dyslipidemia 36%, smoking 39% 86% 63% sedentary and overweight/obesity. with index measurement ankle-brachial 25 (61%) women and 34 (57.6%) men had pathological findings; being more frequent mild peripheral arterial disease in 14 (34.1%) women and 17 (28.8%) males. for early diagnosis of peripheral artery disease, measuring the ankle-brachial index should be performed in all patients with cardiovascular risk factors and come for outpatient from the primary health care, as this disease patients are asymptomatic and it is underdiagnosed and therefore not treated. Keywords: peripheral arterial disease, ankle-brachial index, intermittent claudication, cardiovascular risk